Intención de uso de tecnologías de la Industria 4.0 entre las Pymes agroexportadoras peruanas, utilizando el modelo TAM - Murillo Jarama, Carolyn Sarita (2023)
This research seeks to know how the behavioral intention to use industry 4.0 technologies is conditioned by the following variables: perceived ease of use, perceived usefulness and attitude towards use, by small and medium-sized Peruvian agro-export companies using the methodology of the Model of Technology Acceptance (TAM). For that reason, a virtual survey is applied to a representative sample with the objective of determining the relationship of the variables and if this model is applicable to the Peruvian reality. The present investigation is divided into eight chapters where the national problem is addressed, a bibliographic validation is carried out and where a contrasted is made with other agro-export contexts and both the objectives, and the hypotheses are presented. Based on the results obtained, it is concluded that the TAM model explains the behavioral intention to use industry 4.0 technologies by small and medium-sized agro-export companies in the Peruvian context and the variables indicated in the previous paragraph have a directly proportional condition to the behavioral intention to use industry 4.0 technologies.